Effect of translucency of CAD-CAM ceramic restorative materials and scanning aid conditions on the accuracy of intraoral scans - Jun-Ho Cho; Jung-Suk Han; Hyung-In Yoon (Elsevier, 2023)
Background/purpose: Subsurface scattering from translucent material would affect the digital scans. This study aimed to evaluate the effect of translucency of ceramic restorative materials and scanning aid conditions on the accuracy of intraoral scans. Materials and methods: Identical anatomic contour crowns with ten ceramic restorative materials were fabricated: five zirconia, three lithium disilicate glass-ceramic, and two leucite reinforced glass-ceramic. The models with ceramic crowns were digitized with an intraoral scanner (IOS) and analyzed for accuracy (n = 10) with and without a scanning aid. Scan time efficiency was recorded. Square-shaped specimens with 1.0-mm thickness were fabricated with the same materials, and translucency parameter (TP) values were measured. One-way ANOVA, Welch ANOVA, and a post-hoc pairwise comparison or independent t-test were used for trueness and time analysis, and the F-test was used to examine the precision (α = 0.05). Pearson correlation test was conducted. Results: Significant differences were revealed for trueness with no scanning aid condition and for TP values (P < 0.05). In contrast, no statistically significant differences were observed for trueness with a scanning aid. A strong correlation (r = 0.854, P < 0.01) between TP value and trueness with no scanning aid was revealed. By applying a scanning aid, trueness was improved and scan time efficiency significantly increased (P < 0.05). Conclusion: The translucency of ceramic restorative materials negatively affects the accuracy of IOS scan without a scanning aid; however, the scan accuracy and time efficiency of IOS scanning for ceramic restorations can be improved by applying scanning aid, and prostheses with high quality without unnecessary labor can be produced.